Gambaran Faktor Kejadian ISPA pada Balita di Wilayah Kerja Puskesmas Pijoan Baru Kecamatan Tebing Tinggi Kabupaten Tanjung Jabung Barat Tahun 2019 - Sondang Siahaan; Supriatna Supriatna (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
ISPA in Indonesia often occupies the first sequence of todler pain.Â  Data of P2 ISPA management in Puskesmas Tanjung Jabung Barat in January-August 2018, the number of ISPA cases found in the city was quite high, namely in Puskesmas Pijoan Baru with a total of 1,132 visitors.Â  The aim of this research is to find out the impact of the ISPA on toddlers which include the occupancy of sleep, ventilation, air conditioning, humidity, room humidity, smoking habits, family habits and the use of burned-mosquito repellent. The type of research was descriptive research with a survey approach. This research was implemented in March until May 2019. The population in this researh were toddlers who were positive infected with ISPA and recorded in Puskesmas Pijoan Baru during October-December 2018 that addresed at the work area of Puskesmas Pijoan Baru. The results of the study showed that 80 respondent homes, the occupancy density of sleeping rooms that filled the population was as big as 3.75%, the habit of ventilation which filled the population as much as 15% of the patients, the total age was as much as 65% of the patients, the majority of patients were filled with 25% of total age, and as much as 3.75% of toddlers did not have ISPA. The community is advised to open windows every morning regularly, not smoke inside the house, provide adding ventilation such as fan, using mosquito nets or anti-comfort packages as replacements for burned-mosquito repellent.